A New Species of Triaenodes (Trichoptera: Leptoceridae), based on morphological and molecular data, from Kaeng Khoi Waterfall, Chumphon Province, southern Thailand - PONGSAK LAUDEE; Hans Malicky; Masaki Takenaka; PHUWADON SAWANGARROM; NANNAPHAT SUWANNARAT (Zootaxa, 2025)
A new species of Triaenodes tipmaneei sp. nov. is described and illustrated based on the male and female genitalia. The mitochondrial DNA (mtDNA) cytochrome c oxidase subunit I (COI) of the new species and of the most similar species T. themis Malicky and Prommi 2006 were analyzed. The male genitalia of Triaenodes tipmaneei sp. nov. is distinguished from other species in the genus by the shape of inferior appendages. Inferior appendages of the new species are without recurved processes; the dorsal branch is divided into a dorsal lobe and two processes, with the upper process curved upward and bifid, and the lower process slender and with pointed apex; the main body of the appendage has a short slender apicolateral process, the mesal process is short and pointed, the ventral process is stout, and the apex is pointed. The genetic distance between T. tipmaneei sp. nov. and T. themis, based on the mtDNA COI region, was 8.5 precent, indicating a large genetic differentiation between the two species.
Keywords: Freshwater macroinvertebrate diversity and ecology; Fish biology, ecology, and behavior; Invertebrate Taxonomy and Ecology